Step-by-step explanation:
-4x+1+6-(-9x)
-4x+7-(-9x)
5x+7
Step-by-step explanation:
x=−y−2z+3
x=y+32z+1
x=13y+23z+13
a and d b and c that's the answer
(2x + 3) • (x + 3)
2x • x = 2x^2
2x • 3 = 6x
3 • x = 3x
3 • 3 = 9
6x and 3x combine to get 9x, which when all written out is equal to your original trinomial.
Answer: (b)
Step-by-step explanation:
Given
![\left | p\right |=\dfrac{2}{5}x+2](https://tex.z-dn.net/?f=%5Cleft%20%7C%20%20p%5Cright%20%7C%3D%5Cdfrac%7B2%7D%7B5%7Dx%2B2)
![\left | q\right |=\dfrac{-3}{4}x-1](https://tex.z-dn.net/?f=%5Cleft%20%7C%20%20q%5Cright%20%7C%3D%5Cdfrac%7B-3%7D%7B4%7Dx-1)
![\left | p+q\right |=2x+4](https://tex.z-dn.net/?f=%5Cleft%20%7C%20%20p%2Bq%5Cright%20%7C%3D2x%2B4)
for two complex number, ![z_1,z_2](https://tex.z-dn.net/?f=z_1%2Cz_2)
![\left | z_1+z_2\right |\leq \left | z_1\right |+\left | z_2\right |](https://tex.z-dn.net/?f=%5Cleft%20%7C%20%20z_1%2Bz_2%5Cright%20%7C%5Cleq%20%5Cleft%20%7C%20%20z_1%5Cright%20%7C%2B%5Cleft%20%7C%20%20z_2%5Cright%20%7C)
Apply the above the property
![\Rightarrow 2x+4\leq \dfrac{2}{5}x+2-\dfrac{3}{4}x-1\\\\\Rightarrow 2x+4\leq \dfrac{8x-15x}{20}+1\\\\\Rightarrow 2x+3\leq -\dfrac{7x}{20}\\\Rightarrow x\leq -\dfrac{60}{47}](https://tex.z-dn.net/?f=%5CRightarrow%202x%2B4%5Cleq%20%5Cdfrac%7B2%7D%7B5%7Dx%2B2-%5Cdfrac%7B3%7D%7B4%7Dx-1%5C%5C%5C%5C%5CRightarrow%202x%2B4%5Cleq%20%5Cdfrac%7B8x-15x%7D%7B20%7D%2B1%5C%5C%5C%5C%5CRightarrow%202x%2B3%5Cleq%20-%5Cdfrac%7B7x%7D%7B20%7D%5C%5C%5CRightarrow%20x%5Cleq%20-%5Cdfrac%7B60%7D%7B47%7D)
Also, the absolute value of each complex number must be greater than or equal to zero
![\text{Case-1}\\\\\Rightarrow \dfrac{2}{5}x+2\geq 0\\\\\Rightarrow x\geq -5\\\\\text{Case-2}\\\\\Rightarrow -\dfrac{3}{4}x-1\geq 0\\\\\Rightarrow x\leq -\dfrac{4}{3}\\\\\text{Case-3}\\\\\Rightarrow 2x+4\geq 0\\\Rightarrow x\geq -2](https://tex.z-dn.net/?f=%5Ctext%7BCase-1%7D%5C%5C%5C%5C%5CRightarrow%20%5Cdfrac%7B2%7D%7B5%7Dx%2B2%5Cgeq%200%5C%5C%5C%5C%5CRightarrow%20x%5Cgeq%20-5%5C%5C%5C%5C%5Ctext%7BCase-2%7D%5C%5C%5C%5C%5CRightarrow%20-%5Cdfrac%7B3%7D%7B4%7Dx-1%5Cgeq%200%5C%5C%5C%5C%5CRightarrow%20x%5Cleq%20-%5Cdfrac%7B4%7D%7B3%7D%5C%5C%5C%5C%5Ctext%7BCase-3%7D%5C%5C%5C%5C%5CRightarrow%202x%2B4%5Cgeq%200%5C%5C%5CRightarrow%20x%5Cgeq%20-2)
Taking the intersection of the above values of x, we get